Taxonomy of the genus Megalinus Mulsant & Rey (Coleoptera: Staphylinidae, Xantholinini) and seven new species from China - Zhou, Yu-Lingzi; Bordoni, Arnaldo; Zhou, Hong-Zhang (Zootaxa, 2013)
This paper studies the taxonomy of the genus Megalinus Mulsant & Rey, 1877 (Coleoptera: Staphylinidae, Xantholinini) and offers a comprehensive revision of the Chinese fauna. Seven new species are described: Megalinus ailaoshanensis Zhou & Zhou sp. nov. from Yunnan, M. hailuogouensis Bordoni sp. nov. from Sichuan, M. liupanshanensis Zhou & Zhou sp. nov. from Ningxia, M. ningxiaensis Bordoni sp. nov. from Ningxia, M. nonvaricosus Zhou & Zhou sp. nov. from Ningxia, M. solidus Zhou & Zhou sp. nov. from Hainan and Yunnan, and M. tangi Bordoni sp. nov. from Xizang. The taxonomic status of M. leishanensis (Bordoni, 2007) is reinstated and treated as a valid species here. The following new synonym is proposed: M. suffusus (Sharp, 1874) = L. flavoelytratus (Bordoni, 2007) syn. nov. Three species originally described in Chinese are redescribed here: M. cinnamomeus (Zheng, 1994), M. coracinus (Zheng, 1994) and M. zhenyuanensis (Zheng, 1994). Therefore the Chinese fauna of the genus Megalinus is now represented by a total of 33 species. A key to all Chinese species is provided.